Notes on Early Land Plants Today. 33. Notes on Anastrophyllaceae (Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Konrat, Matt Von (Phytotaxa, 2013)
Anastrophyllum paramicola was described by Schuster (2002a) as being remotely allied to Anastrophyllum donnianum (Hooker 1813: 39) Stephani (1893: 140) and Anastrophyllum assimile (Mitten 1860: 93) Stephani (1893: 140). However, Schuster did not at all mention the relatively common Anastrophyllum nigrescens and the description match that species well.